Strategi Penelusuran Informasi yang Efektif Menggunakan Internet terhadap Siswa/I di SMA Negeri 1 Percut Sei Tuan - Asmita Khoiriyah Manurung; Nur Santri; Reni Ayu Pratiwi; Dian Ramadani; Franindya Purwaningtyas (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
Advances in information technology also bring fundamental changes in meeting the information needs needed. One of these technologies is the internet, which is an unlimited source of information and can be accessed anytime and anywhere for 24 hours. While printed sources have limited access, namely the place and time and the novelty of the collection. This study aims to find out the information that students are looking for through internet services. The research method used is this research method is qualitative research. The results showed that most of the students taught themselves to search for information through the internet (64.29%), while the frequency of using the internet to search for information was often (70.83%) carried out by most of the students in the library, and in this study half of the respondents' answers stated that students only use the internet once (50%) in one visit to the library, and almost half of the respondents' answers stated that students use the internet during breaks (41.46%). Keywords: search, information, internet